2016
DOI: 10.7314/apjcp.2016.17.1.407
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Cancer Epidemiology in Iran: a Time Trend Study

Abstract: Background: Considering the rising incidence of thyroid cancer worldwide, the aim of our study was to investigate the temporal trends in the incidence of this cancer in a large population of Iranian patients. Materials and Methods: We used the Iran Cancer Data System (ICDS) Registry to assess the thyroid cancer trend from 2004 to 2010 with regard to different genders, age groups, and morphologies. To do this we analyzed the data of 10,913 new cases of thyroid cancer that occurred during these years. Results: T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 36 publications
4
41
0
Order By: Relevance
“…In this study, the mean age of patients with thyroid cancer was 41.9 years. This is comparable with a previous study of the Iranian population that reported a mean age of 45 years (4). A study performed in Isfahan, Iran, reported the prevalence of thyroid incidentaloma as 13.2% that was more prevalent in females than in males (21).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In this study, the mean age of patients with thyroid cancer was 41.9 years. This is comparable with a previous study of the Iranian population that reported a mean age of 45 years (4). A study performed in Isfahan, Iran, reported the prevalence of thyroid incidentaloma as 13.2% that was more prevalent in females than in males (21).…”
Section: Discussionsupporting
confidence: 89%
“…In agreement with previous publications, the current study showed a higher period prevalence in females with a value of 49.3 than in males with a value of 13.3 (per 100000 persons), with a significant difference (chi-squared test; P < 0.001). Safavi et al in 2016 reported a female-male ratio of 2 (4). In this study, the PP was 3.7 times higher in females than in males.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Thyroid cancer is relatively infrequent malignancy, which accounts for about 1-5% of the cancer cases in women and less than 2% in men [1]. Although, it is one of the most common cancer among endocrine malignancies accounting for more than 95% of new cases in the United States [2,3], according to American Cancer Society, thyroid cancer in the United States in 2019 is estimated to be about 53,070 new cases (40,260 in men and 37,810 in woman), and more than 2000 people will die from the disease [3].…”
Section: Introductionmentioning
confidence: 99%
“…As well as in the rest of the world, the incidence of thyroid cancer has increased threefold over the past 30 years and is expected to increase by 50-60% between 2010 and 2020 [3][4][5]. The increase in thyroid cancer incidence rates could be explained by thyroid ultrasound screening with improved technical performance of the equipment, as well as better access to medical examination [1,6].…”
Section: Introductionmentioning
confidence: 99%